Insight into the thermodynamic response characteristics in a liquid helium-4 tank using a modified Lee model: A numerical study - Caigong Zhang; Shaomu Wen; Zhixiang Dai; Changjun Li; Ping Tang; Wenyan Zhang; Xue Zhong; Yang Peng (Process Safety and Environmental Protection, 2026)

Optimizing thinning intensity for large-diameter poplar plantations: A UAV-LiDAR-based growth assessment - Tianle Li; Chenyan Lv; Qiang Guo; Dongdong Li; Bin Dong; Xuehai Tang; Junlong Liu; Tingting Miao; Changjun Ding; Youquan Jiao; Xiang Gao (Forest Ecology and Management, 2025)

An Unmanned Vessel Path Planning Method for Floating-Waste Cleaning Based on an Improved Ant Colony Algorithm - Yong Li; Changjun Tang; Sen Yan; Ruichen Wang; Dongxu Gao (Journal of Marine Science and Engineering, 2025)
Efficient cleaning of floating waste using an intelligent unmanned surface vehicle is an important development trend in inland water governance. Path planning is the core of the decision-making module for unmanned surface vehicle waste cleaning and is key to achieving autonomous operation of the unmanned surface vehicle. However, due to the complexity and dynamic changes of the water surface environment, unmanned surface vehicle path planning methods for floating waste face challenges such as small size, uncertainty, and uneven distribution of floating waste. In response to the above issues, this article studies the problem of insufficient integration and low efficiency between existing path planning algorithms and target-perception modules, and designs an efficient overall path planning method for floating-waste cleaning by an unmanned surface vehicle. This method transforms the path planning problem of floating-waste cleaning unmanned surface vehicle into a Traveling Salesman Problem by setting global patrol points and tracking local targets, and proposes an improved ant colony algorithm, IACO, to solve the Traveling Salesman Problem. This article is based on the TSPLIB dataset and practical applications for experiments. The experimental results show that the proposed method has average optimal path lengths of 75.930 m, 446.555 m, and 703.759 m on the Ulysses22, eil51, and st70 datasets, respectively, which are reduced by 0.355 m, 4.108 m, and 13.575 m compared to the benchmark.

SIRT5 alleviates oxidative stress of boar sperm induced by cryopreservation through IDH2 and SOD2 pathway - Malik Ahsan Ali; Yan Zhang; Qingyong Ni; An-qi Huang; Shan Dou; Yiguo Tang; Xinhong Xu; Changjun Zeng (Theriogenology, 2025)

Development of a novel ternary MOF nanozyme-based smartphone-integrated colorimetric and microfluidic paper-based analytical device for trace glyphosate detection - Ting Zhang; Miao Tang; SiYi Yang; Huanbao Fa; Yongzhong Wang; Danqun Huo; Changjun Hou; Mei Yang (Food Chemistry, 2025)

Supramolecular porous phase change materials for encapsulation of nitrate with amino-expanded graphite by cucurbit[7]uril - Jingxin Kang; Huihui Wang; Changjun Zou; Yuqin Li; Jianwei You; Enxing Liu; Wenyue Tang; Yezhong Wang; Bo Wen; Yixuan Cao (Journal of Cleaner Production, 2024)

Exploring the biogeography, morphology, and phylogeny of the condylostomatid ciliates (Alveolata, Ciliophora, Heterotrichea), with establishment of four new Condylostoma species and a revision including redescriptions of five species found in China - Yong Chi; Fan Wei; Danxu Tang; Changjun Mu; Honggang Ma; Zhe Wang; Khaled A. S. Al-Rasheid; Hunter N. Hines; Xiangrui Chen (Marine Life Science & Technology, 2024)
Species of the ciliate class Heterotrichea Stein, 1859 are a cosmopolitan group of unicellular eukaryotic microorganisms, many of which have been widely used as models in various fields of research such as regenerative biology, functional ecology, environmental toxicology, and symbiotic behavior. However, species identification in the heterotrich family Condylostomatidae, especially the most species-rich and type genus Condylostoma Bory de Saint-Vincent, 1824, remains challenging due to incomplete original descriptions, few reliable distinguishing characters, and overlapping features between different species. This study presents an updated revision of Condylostoma and its related genus Condylostomides da Silva Neto, 1994 based on descriptions of five species, including nine populations collected from China, using both morphological and molecular methods. The main findings are as follows: (1) 43 nominal species and about 130 populations are reviewed, resulting in the recognition of 30 valid species of Condylostoma and eight valid species of Condylostomides ; (2) keys, synonyms, biogeographic distributions and amended/improved diagnoses of all valid species are provided; (3) based on the available data, four new Condylostoma species ( C. marinum sp. nov., C. petzi sp. nov., C. villeneuvei sp. nov., and C. microstomum sp. nov.), one new combination ( Condylostomides minimus (Dragesco, 1954) comb. nov. & nom. corr.), and two corrected names ( Condylostoma ancestrale Villeneuve-Brachon, 1940 nom. corr. and Condylostomides nigrus (Dragesco, 1960) nom. corr.) are suggested; (4) cryptic species are detected and proposed for the first time to form the Condylostoma curvum species complex; (5) three highly confusing Condylostoma species, C. kris , C. spatiosum , and C. minutum , are redefined for the first time based on modern taxonomic methods; (6) a ‘flagship’ species, Condylostomides coeruleus , is recorded for the first time from the continent of Asia, substantially expanding its biogeography; (7) ciliature adjacent to the distal end of the paroral membrane within the family Condylostomatidae is uniformly defined as frontal membranelles and is classified into three patterns according to the arrangement of kinetosomes, which serve as important key features.

Intelligent treatment of tannery wastewater via H2O2 photocatalytic oxidation coupled adsorption process - Huimin Yu; Miaomiao Tang; Jian He; Changjun Liu; Pan Wu; Wei Jiang (Journal of Water Process Engineering, 2024)

Developmental regulation of conserved non-coding element evolution provides insights into limb loss in squamates - Zeng Wang; Changjun Peng; Wei Wu; Chaochao Yan; Yunyun Lv; Jia-Tang Li (Science China Life Sciences, 2023)

Assessing the efficacy of bleaching powder in disinfecting marine water: Insights from the rapid recovery of microbiomes - Yawen Tang; Huajun Zhang; Jiaojiao Yan; Nan Luo; Xuezhi Fu; Xiaoyu Wu; Jialin Wu; Changjun Liu; Demin Zhang (Water Research, 2023)

Effects of poplar agroforestry systems on soil nutrient and enzyme activity in the coastal region of eastern China - Cheng Xu; Zhuangzhuang Qian; Bo Wang; Tao Yang; Zeyang Lin; Di Tian; Changjun Ding; Luozhong Tang (Journal of Soils and Sediments, 2023)

The effective removal of phenol from aqueous solution via adsorption on CS/β-CD/CTA multicomponent adsorbent and its application for COD degradation of drilling wastewater - Hong Peng; Changjun Zou; Chengjun Wang; Wenyue Tang; Juxian Zhou (Environmental Science and Pollution Research, 2020)

Proteomic Analysis of Vibrio parahaemolyticus Under Cold Stress - Jing Tang; Juntao Jia; Ying Chen; Xiaohua Huang; Xiaoliang Zhang; Liqing Zhao; Wei Hu; Changjun Wang; Chao Lin; Zhenxing Wu (Current Microbiology, 2018)

A functional variant in miR-143 promoter contributes to prostate cancer risk - Haiyan Chu; Dongyan Zhong; Jialin Tang; Jie Li; Yao Xue; Na Tong; Chao Qin; Changjun Yin; Zhengdong Zhang; Meilin Wang (Archives of Toxicology, 2016)

A two-tube multiplex real-time RT-PCR assay for the detection of four hemorrhagic fever viruses: severe fever with thrombocytopenia syndrome virus, Hantaan virus, Seoul virus, and dengue virus - Zhifeng Li; Xian Qi; Minghao Zhou; Changjun Bao; Jianli Hu; Bin Wu; Shenjiao Wang; Zhongmin Tan; Jianguang Fu; Jun Shan; Yefei Zhu; Fenyang Tang (Archives of Virology, 2013)

Inactivation of Dipeptidyl Peptidase IV Attenuates the Virulence of Streptococcus suis Serotype 2 that Causes Streptococcal Toxic Shock Syndrome - Junchao Ge; Youjun Feng; Hongfeng Ji; Huimin Zhang; Feng Zheng; Changjun Wang; Zhimin Yin; Xiuzhen Pan; Jiaqi Tang (Current Microbiology, 2009)

Identification and Experimental Verification of Protective Antigens Against Streptococcus suis Serotype 2 Based on Genome Sequence Analysis - Lina Liu; Gong Cheng; Changjun Wang; Xiuzhen Pan; Yanguang Cong; Qu Pan; Jing Wang; Feng Zheng; Fuquan Hu; Jiaqi Tang (Current Microbiology, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)